The Conception of Social Integration in Islam: example of Madina - Samedov, Vugar (Scholarya Demo Journal of Ruby, 2019)
The article deals with the process of establishment of a new society by the Prophet. Religion has a great role in the integration of people. Individuals belonging to the same religion have the feeling of affiliation. Islamic society is based on the concept of tawheed. At the same time, the prophet united the institutions such as clan, tribe, ashirah which were based on fanaticism under one social structure called ummah based on equality principle. The concept of ummah does not eliminate the existence of tribes; it only eliminates harmful beliefs. Undoubtedly, the role of fraternity in the social integration of Muslim society in the early period Medina is significant. Hazrat Mohammad achieved to reconcile strong Muslims with the weak ones who were opressed in Mecca. Later, he reconciled the Ovs and Khazraj tribes living in Medina constructing an exemplary society for the people of Mecca and Medina. The Prophet’s charismatic personality played an important role in this integration. Undoubtedly, agreements play particular role in the integration process of society. From this point of view, Medina treaty plays a major role in the integration of a disintegrated society.